The Influence of Inflation, Mental Accounting, and Risk Aversion on Investment Decisions with Financial Literacy as a Moderating Variable - Putu Dewi Pratiwi Pradnyasari; Ni Kadek Sinarwati; I Gusti Ayu Purnamawati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study examines the influence of inflation, mental accounting, and Risk Aversion on investment decisions, with financial literacy as a mediating variable among stock investors in the Province of Bali. Data collection was conducted using a questionnaire containing a series of statements related to each variable studied, as well as interviews with two investment practitioners to support the questionnaire results. The respondents of this study were stock investors residing in Bali Province who have been actively investing for more than one year. The sample consisted of 400 respondents. Data analysis was conducted using the SmartPLS 2.0 software. Hypothesis testing using the PLS approach was carried out in two stages: the outer model and the inner model testing. The outer model test was conducted to validate the reliability and validity of all indicators for each variable. The inner model test was conducted to examine the relationships among variables based on the established hypotheses. The results of the study indicate that (1) Inflation has a positive and significant effect on investment decisions; (2) Mental accounting has a positive and significant effect on investment decisions; (3) Risk Aversion has a negative and significant effect on investment decisions; (4) Financial literacy weakens the effect of inflation on investment decisions; (5) Financial literacy strengthens the effect of mental accounting on investment decisions, and (6) Financial literacy weakens the effect of Risk Aversion on investment decisions.